2021
DOI: 10.3389/fped.2021.734753
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Flow Rate Escalation for Pediatric Patients on High Flow Nasal Cannula Using Machine Learning

Abstract: Background: High flow nasal cannula (HFNC) is commonly used as non-invasive respiratory support in critically ill children. There are limited data to inform consensus on optimal device parameters, determinants of successful patient response, and indications for escalation of support. Clinical scores, such as the respiratory rate-oxygenation (ROX) index, have been described as a means to predict HFNC non-response, but are limited to evaluating for escalations to invasive mechanical ventilation (MV). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…They found that an ROX index above 66.7 at 24 hours after HFNC had 86% sensitivity, 79% specificity, 23.1% PPV, and 98.8% NPV. A previous retrospective study by Krachman et al [ 16 ] used machine learning algorithms of ROX index to predict flow rate escalation. In the present study, we used the normal RR for age to adjust the ROX index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that an ROX index above 66.7 at 24 hours after HFNC had 86% sensitivity, 79% specificity, 23.1% PPV, and 98.8% NPV. A previous retrospective study by Krachman et al [ 16 ] used machine learning algorithms of ROX index to predict flow rate escalation. In the present study, we used the normal RR for age to adjust the ROX index.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study by Krachman et al. (17) used machine learning algorithms of ROX index to predict flow rate escalation. In the present study, we used the normal RR for age to adjust the ROX index.…”
Section: A C C E P T E Dmentioning
confidence: 99%